Biochar and bentonite application improves aeolian sandy soil health and enhances soil carbon sequestration and emission reduction potential - Liang Weijing; Tang Jiaxi; Li Yu; Song Sizhu; Jiang Xiaoyu; Hao Liyu; Tao Shuyu; He Miaomiao (Scientific Reports)
Abstract Aeolian sandy soil is barren and readily leads to low fertilizer utilization rates and yields. Therefore, it is imperative to improve the water and fertilizer retention capacity of these soils. In this paper, three kinds of biochar (rice husk, corn stalk, and bamboo charcoal) and bentonite were used as amendments in the first year of the experiment. In the second year, only corn stalk biochar was applied. The effects of biochar and bentonite on the physicochemical and biological characteristics of aeolian sandy soil and corn agronomic traits were studied through a 2-year field experiment, and the carbon sequestration and emission reduction potential of biochar in aeolian sandy soil were explored. The results showed that the input of biochar and bentonite effectively improved water content and reduced soil bulk density. Compared with the same treatment in the first year, the content of water-stable aggregates with particle sizes greater than 0.25 mm, mean weight diameter and geometric mean diameter of the corn stalk biochar mixed with bentonite treatment significantly increased in the second year. Biochar and bentonite significantly increased the soil organic matter content, pH, cation exchange capacity (CEC) and available nitrogen, phosphorus and potassium contents, and CEC increased by 150.4%. Soil available phosphorus increased 2.6 times compared with that of the fertilizer treatment. Soil alkali-hydrolyzable nitrogen content increased by 211.5%, respectively. The plant height, leaf area index and ground dry matter mass also increased significantly, and the corn yield increased by 36.6% in response to the mixed application of 1.9 t/hm2 corn stalk biochar and 12 t/hm2 bentonite. The contents of urease, sucrase and catalase increased first and then decreased with crop growth through the jointing, silking and maturity stages. The microbial carbon content increased 2.4 times in the second year when corn stalk biochar was applied compared with that in the first year. The carbon sequestration potential of biochar application was equivalent to offsetting CO2 emissions by approximately 100 million tons per year of the study.